The Subclasses of Analytic Functions of Complex Order with Application of q-Derivative Operators - Aini Janteng; Desmond Lee Ching Yiing; Yong Enn Lun; Jaludin Janteng; Lee See Keong; Rashidah Omar; Andy Liew Pik Hern (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
In this article, we represent A as the of analytic functions in the open unit disk. Further, new subclasses of analytic functions of complex order utilising q-derivative operator are generated. The subclasses are symbolised by Hq,b(ϕ) and Iq,b(ϕ). Additionally, we discover that these function classes are implicated with the Fekete-Szegö inequalities.